Arteriovenous fistula following radial artery cannulation in a patient with vascular Ehlers-Danlos syndrome - Gabrielle Gionet, MD; Félix H. Savoie-White, MD, MSc; Ievgen Gegiia, MD, MSc; Sara Sédillot-Daniel, MD, MSc; Violaine Dalens, MD; Pascal Rhéaume, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Vascular Ehlers-Danlos syndrome (VEDS) increases the risk of complications following invasive procedures owing to vascular fragility. This case report details a patient with VEDS who developed two arteriovenous fistulas after radial line placement for an emergency endovascular procedure. Effective management required ligation of the radial artery feeding both two arteriovenous fistulas, underscoring the need to minimize invasive procedures and ensure thorough follow-ups in patients with VEDS. Regular imaging and proactive monitoring are essential for the early detection and management of complications, thereby improving patient outcomes and decreasing long-term risks.